USING FISHBOWL METHOD IN ENGLISH LESSONS AS FOREIGN LANGUAGE (ResearchJet Journal of Analysis and Inventions, 2021)
The article discusses the use of fishbowl method in English Lessons.The stages of application,advantages and disadvantages are explained.